Merdeka Belajar Kampus Merdeka Based Curriculum Design for the Sharia Accounting Study Program at Islamic University - Andi Patimbangi; Rahma Hidayati Darwis (STAI Hubbulwathan Duri, 2023)
This research aims to understand the concept of independent learning better so that an Islamic accounting curriculum can incorporate it into the design of learning activities. Conducting preliminary research is the initial stage in the process of adopting and altering Borg Gall's development processes. Analyse the current course of study to investigate the existing data and do preliminary research. This is crucial. The study's results demonstrate that Islamic accounting programmes may readily integrate the concept of independent learning into their curricula, particularly through student exchange and Thematic Community Service Program (KKN). This research evaluates the program's strengths, weaknesses, prospects, and challenges, as well as the policies and preparations made by the leadership at the Islamic Faculty of Economics and Business to provide the two programmes. The implementation of the programme may be hindered by issues such as information systems that are not interoperable with each other and academic calendars that require adjustments for each location. This holds particularly true for student exchange programmes. Partners may also under pressure to establish governance for the MBKM programme, even though they have just recently become aware of it.